Timeless evolution of walking and pace strategy of women’s race walking - Panagiotα Fitili (Pedagogy of Physical Culture and Sports, 2020)
Background and Study Aim. The purpose of this research was to study the timeline evolution of walking, as well as the Pacing Strategy Profiles of high-level women in the 20 km of race walking. Material: The practical example of applying the theoretical basis was made during the Women’s Greek Championship (Megara 2016), in which 12 athletes aged 19 to 40 participated (28.50 ± 7.20).